Gas permeable mold for defect reduction in nanoimprint lithography - Mizui, Kento; Hanabata, Makoto; Takei, Satoshi (SPIE, 2019)
In recent years, nanoimprint lithography is applied to manufacturing of optical materials and biosensor. However, void and generated gas are caused pattern failures. We proposed cellulose based gas permeable molds to reduce pattern failures. In this research we could raise the mold reproducibility by using the under-layer coating and liquid release agent. It was confirmed that imprinting materials including 10 wt% each of acetone, cyclopentane, and propylene glycol methyl ether acetate (PGMEA) as volatile solvents could also be imprinted accuracy and number of imprinting times were increased. In addition, we succeeded in expand the cellulose based gas permeable mold size 5 times as compared with the conventional cellulose based gas permeable mold by using step and repeat process and large scale quartz mold. Various manufacturing can be expected by increasing the repeatability and the pattern area of the cellulose based gas permeable mold.